Determination of sp³ fraction in ta-C coating using XPS and Raman spectroscopy - Zavaleyev, V.; Walkowicz, J.; Sawczak, M.; Klein, M.; Moszyński, D.; Chodun, R.; Zdunek, K. (Вопросы атомной науки и техники, 2016)
The paper presents results of studies on the structure of tetrahedral amorphous carbon films (ta-C) with a
thickness in the range from 20 to 280 nm, deposited using pulsed vacuum arc technique with an electromagnetic
Venetian blind plasma filter. The results of the phase structure analysis, obtained using visible Raman spectroscopy
and UV Raman spectroscopy methods, showed a strong dependence of the results on the presence, on the surface of
synthesized thin carbon films, even of a minimum number of microparticles. The presence of microparticles in the
deposited coatings strongly affects the accuracy of the measured data, used next for calculation the ID/IG, IT/IG ratios
and determination of the G-peak dispersion, for all coating thicknesses, which pointed to significant diversification
in sp³ -bonds content in deposited films. Представлены результаты исследования структуры тетраэдральных аморфных углеродных пленок (tа-С)
толщиной в интервале 20…280 нм, осажденных методом импульсной вакуумной дуги с электромагнитным
жалюзи плазменного фильтра. Результаты фазово-структурного анализа, полученные методами
спектроскопии комбинационного рассеяния света в видимом и УФ-диапазонах, демонстрируют сильную
зависимость результатов от наличия на поверхности тонких углеродных пленок микрочастиц даже в
минимальном количестве. Присутствие микрочастиц в осажденных покрытиях сильно влияет на точность
измеренных данных, используемых далее для вычисления соотношений ID/IG, IT/IG и определения дисперсии
G-пика для покрытий всех толщин, что приводит к значительному разбросу данных при оценке связей в
осажденных пленках. Представлені результати дослідження структури тетраедральних аморфних вуглецевих плівок (tа-С)
завтовшки в інтервалі 20…280 нм, осаджених методом імпульсної вакуумної дуги з електромагнітним
жалюзі плазмового фільтра. Результати фазово-структурного аналізу, що отримані методами спектроскопії
комбінаційного розсіяння світла у видимому і УФ-діапазонах, демонструють велику залежність результатів
від наявності на поверхні тонких вуглецевих плівок мікрочасток навіть у мінімальній кількості. Присутність
мікрочасток в осаджених покриттях дуже впливає на точність виміряних даних, що використовувалися для
обчислення співвідношень ID/IG, IT/IG і визначення дисперсії G-піка для покриттів усієї товщини, що
призводить до значного розкиду даних при оцінці зв'язків в осаджених плівках.